Photonic Curing of Nickel Oxide Transport Layer and Perovskite Active Layer for Flexible Perovskite Solar Cells: A Path Towards High-Throughput Manufacturing - Piper, Robert T.; Daunis, Trey B.; Xu, Weijie; Schroder, Kurt A.; Hsu, Julia W. P. (Frontiers in Energy Research, 2021)
High-throughput roll-to-roll (R2R) manufacturing of perovskite solar cells (PSCs) is currently limited by thermal processes that take tens of minutes each, translating to impractically long annealing tools at high web speeds. In addition, PSCs are usually made with metal oxide transport layer materials that require high temperatures for thermal annealing. Here, we demonstrate the fabrication of PSCs using photonic curing, instead of thermal annealing, to convert NiOx directly from sol-gel precursors for hole transport layers and to crystallize methylammonium lead iodide (MAPbI3) active layers on flexible Willow® Glass substrates. Photonic curing uses short, intense pulses of light to process materials at a high speed, hence it is compatible with R2R manufacturing. We achieved power conversion efficiencies (PCEs) of 11.7% in forward-scan and 10.9% in reverse-scan for PSCs made with photonic cured NiOx and MAPbI3 films. Furthermore, both NiOx and MAPbI3 films could be processed with a single photonic curing pulse, with a web speed of 5.7 m/min, and still produce PCEs comparable to thermally annealed control samples. Based on the single-pulse photonic curing condition for each film, we project a web speed of 26 m/min, laying a pathway to high-throughput production of perovskite solar modules.